Organocatalytic asymmetric fluorination of α-chloroaldehydes involving kinetic resolution - Shibatomi, Kazutaka; Okimi, Takuya; Abe, Yoshiyuki; Narayama, Akira; Nakamura, Nami; Iwasa, Seiji (Beilstein Journal of Organic Chemistry, 2014)
In a previous study it was shown that the enantioselective α-fluorination of racemic α-chloroaldehydes with a chiral organocatalyst yielded the corresponding α-chloro-α-fluoroaldehydes with high enantioselectivity. It was also revealed that kinetic resolution of the starting aldehydes was involved in this asymmetric fluorination. This paper describes the determination of the absolute stereochemistry of a resulting α-chloro-α-fluoroaldehyde. Some information about the substrate scope and a possible reaction mechanism are also described which shed more light on the nature of this asymmetric fluorination reaction.
Keywords: α-branched aldehyde; asymmetric catalysis; chlorination; fluorination; organocatalyst; organo-fluorine